Multisectoral Strategies To Address Stunting Among Fisherfolk Children: An Evidence-Based Literature Review - Zuardin (International Conference on Sustainable Health Promotion, 2025)
Stunting among children in coastal fishing communities remains a critical public health issue, with prevalence rates often exceeding national averages. This literature review synthesizes findings from 50 peer-reviewed studies focusing on nutritional status, food security, sanitation, and socio-cultural factors contributing to stunting among fisher families. Despite abundant marine resources, children in fishing communities continue to face high risks of undernutrition due to limited economic access to diverse and nutritious food, poor maternal education, inadequate sanitation, and deeply rooted cultural feeding practices. The review highlights that household food insecurity, low dietary diversity, and misconceptions about protein-rich foods (e.g., fish and eggs) significantly affect child growth outcomes. Environmental conditions, such as a lack of clean water and poor waste management, exacerbate infection risks, further impairing nutrition. Effective interventions require a multisectoral approach that integrates community-based nutrition education, promotion of local marine foods, improvement of sanitation infrastructure, and economic empowerment of fisher households. Culturally adapted strategies that involve both mothers and fathers have shown promise in improving child nutrition outcomes. Addressing stunting in coastal communities demands not only technical solutions but also attention to social justice, cultural context, and sustainable livelihoods.